Investigation of tumour supressor protein p53 in renal cell carcinoma patients - Hodorova, Ingrid; Solar, Peter; Mihalik, Jozef; Vecanova, Janka; Adamkov, Marian; Rybarova, Silvia (Biomedical papers, 2014)
Background: Investigation of p53 immunoreactivity in formalin-fixed paraffin-embedded tissues of normal renal tissue and renal cell carcinoma with respect to histopathologic subtype and nuclear grade of RCC.Methods: 42 tissue sections of RCC and 5 samples of normal renal tissue were stained for p53 expression using immunohistochemical assay. The results were analyzed in relation to nuclear grade and histopathologic subtype.Results: In total, p53 expression was found to be 4 to 5 times higher (30.8%) in other types of RCC than in the clear-cell type of RCC (6.9%). Further, there was no statistically significant difference in p53 overexpression among the histopathologic subtypes (P>0.05, P=0.063). No association was found between the expression of p53 and nuclear grade (P>0.05, P=0.17). Interestingly, our study also showed weak cytoplasmic positivity in renal tubular epithelium.Conclusion: Our findings suggest that p53 might play an important role in tumour development or progression and it might be used as a new predictor and therapeutic target for RCC.
Keywords: renal cell carcinoma; expression of p53; immunohistochemistry